Transportation Access in the Transition to Adulthood: Navigating a Neurotypical World on the Autism Spectrum - Wilson, John S.; Eilenberg, Jenna; Feng, Wenyan; Chu, Andrea; Abramson, Mathena A.; Davis, Kathryn A.; Guthrie, Kate M.; Kuhn, Jocelyn; Orsmond, Gael I.; Long, Kristin A. (Journal of autism and developmental disorders, 2025)
Despite documented transportation access challenges among autistic adolescents and young adults (AYAs), little is known about the processes through which transportation inaccessibility affects AYAs during the transition to adulthood. This qualitative analysis explores what underlies challenges for AYAs who have trouble accessing transportation in the transition to adulthood, how this inaccessibility affects their transition process, and suggestions for supporting AYAs in accessing transportation in the future. Semi-structured qualitative interviews were conducted with 27 culturally, linguistically, and economically diverse parents/caregivers of AYAs and five service providers. Data were systematically coded, organized using Framework Matrices, and analyzed using Applied Thematic Analysis. Findings reveal how barriers affect AYAs' transportation access, including (1) mismatches between transportation environments and AYAs' sensory, interpersonal, and executive functioning needs and (2) few opportunities for AYAs to develop skills and adaptations to use available transportation options and/or to identify alternative transportation options. Although transportation barriers were described broadly, their impact on minoritized and low-income AYAs was more pronounced, thus widening transition-related disparities. Findings highlight compounding barriers to and implications of transportation inaccessibility for autistic youth. The study suggests the importance of a multi-tiered approach to improving transportation accessibility for AYAs, including ensuring dedicated transportation education, improving community and institutional partnerships, and re-designing transportation infrastructure, which together have the potential to improve transition-related and adult outcomes. Future research should prioritize partnering with AYAs to design and implement interventions to improve transportation access.